Perilaku Petani Anggota Subak Abian dalam Pengendalian Hama Terpadu Tanaman Kakao (Theobroma cacao) (Kasus Subak Abian Sida Karya, Banjar Petang, Desa Petang, Kecamatan Petang, Kabupaten Badung) - SITORUS, JOHANES MARULITUA; SUARDI, I DEWA PUTU OKA; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.4, Oktober 2016, 2016)
The Behavior of Farmers of Subak Abian toward the Integrated Pest Management of Cocoa Plants (Theobroma cacao) (A Case for Subak Abian Sida Karya, Banjar Petang, Petang Village, Petang Distrik, Badung Regency) Market demand for cocoa is quite high but can not be met by the farmers. The reason is the presence of pests and diseases, and lack of understanding of farmers on Integrated Pest Management. Based on these problems, then Integrated Pest Management Field School (SLPHT) activities are held with the aim of maximizing the role of farmers to be able to control pests and diseases but still pay attention to the environmental sustainability. The purpose of this study is to determine the level of farmers’ knowledge, attitudes, and the implementation of Integrated Pest Management of cocoa trees. The research method is inspired on a Likert scale and the data analysis method used is descriptive qualitative. Total population is assigned as many as 23 people who were participants of the SLPHT. The results of survey revealed that the behavior of farmers of Subak Abian in integrated pest management of cocoa plants  are in good category with the achievement of 76.12%. Recommendation that  can be given to farmers in order to take care of rorak, conserve natural enemies, and be able to multiply Beauveria bassiana independently so that the attacks of pests and cocoa plant diseases can be well controlled.
Keywords: integrated pest management, behavior, knowledge, attitudes, application